Neurological pathophysiology of SARS‐CoV‐2 and pandemic potential RNA viruses: a comparative analysis. Issue 23 (22nd November 2021) - Chakravarty, Nikhil; Senthilnathan, Thrisha; Paiola, Sophia; Gyani, Priya; Castillo Cario, Sebastian; Urena, Estrella; Jeysankar, Akash; Jeysankar, Prakash; Ignatius Irudayam, Joseph; Natesan Subramanian, Sumathi; Lavretsky, Helen; Joshi, Shantanu; et al.
Abstract : SARS‐CoV‐2 has infected hundreds of millions of people with over four million dead, resulting in one of the worst global pandemics in recent history. Neurological symptoms associated with COVID‐19 include anosmia, ageusia, headaches, confusion, delirium, and strokes. These may manifest due to viral entry into the central nervous system (CNS) through the blood–brain barrier (BBB) by means of ill‐defined mechanisms. Here, we summarize the abilities of SARS‐CoV‐2 and other neurotropic RNA viruses, including Zika virus and Nipah virus, to cross the BBB into the CNS, highlighting the role of magnetic resonance imaging (MRI) in assessing presence and severity of brain structural changes in COVID‐19 patients. We present new insight into key mutations in SARS‐CoV‐2 variants B.1.1.7 (P681H) and B.1.617.2 (P681R), which may impact on neuropilin 1 (NRP1) binding and CNS invasion. We postulate that SARS‐CoV‐2 may infect both peripheral cells capable of crossing the BBB and brain endothelial cells to traverse the BBB and spread into the brain. COVID‐19 patients can be followed up with MRI modalities to better understand the long‐term effects of COVID‐19 on the brain. Abstract : Coronaviruses and pandemic‐potential RNA viruses can reach the brain using various mechanisms and thereby induce neurological symptoms. Structural analysis of SARS‐CoV‐2 neuronal entry co‐receptor NRP1 interacting with the Spike protein revealed key mutations among existing variants of concern, which could affect NRP1 binding and SARS‐CoV‐2 spread into the brain. Utilization of MRI modalities would be crucial for tracking viral‐mediated structural changes to the brain.